Stress Analysis of Pressing Joint of Two Conical Pipes - Jančo Roland (Journal of Mechanical Engineering, 2023)
This paper presents a stress analysis of a pressed joint of two conical pipes with the aim to find out whether this kind of connection is suitable for telecommunication masts. The analysis can be considered a complex spatial problem of a thin-walled shell, where the local bending stress influence might be dominant. In this paper a solution using engineering approach and numerical analysis with finite element method (FEM) will be compared.